(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
A mild and efficient method has been developed for the preparation of 14-aryl-14H dibenzo[a,j]xanthenes from one-pot condensation of aldehydes with Î²-naphthol using catalytic amount of Chloroaluminate ionic liquid (imidazolium chlorideÂ·3AlCl3 or pyridiniumchlorideÂ·3AlCl3) under thermal solvent-free conditions. Excellent yields, short reaction times, easy workup and reusability of the catalyst as well as solvent free conditions are advantages of this procedure.